Low-cost plasmonic solar cells prepared by chemical spray pyrolysis - Kärber, Erki; Katerski, Atanas; Oja Acik, Ilona; Mikli, Valdek; Mere, Arvo; Sildos, Ilmo; Krunks, Malle (Beilstein Journal of Nanotechnology, 2014)
Solar cells consisting of an extremely thin In2S3/CuInS2 buffer/absorber layer uniformly covering planar ZnO were prepared entirely by chemical spray pyrolysis. Au nanoparticles (Au-NPs) were formed via thermal decomposition of a gold(III) chloride trihydrate (HAuCl4·3H2O) precursor by spraying 2 mmol/L of the aqueous precursor solution onto a substrate held at 260 °C. Current–voltage scans and external quantum efficiency spectra were used to evaluate the solar cell performance. This work investigates the effect of the location of the Au-NP layer deposition (front side vs rear side) in the solar cell and the effect of varying the volume (2.5–10 mL) of the sprayed Au precursor solution. A 63% increase (from 4.6 to 7.5 mA/cm2) of the short-circuit current density was observed when 2.5 mL of the precursor solution was deposited onto the rear side of the solar cell.
Keywords: Au nanoparticles; chemical spray pyrolysis; extremely thin absorber; plasmon resonance; solar cell

(untitled) - Ferry, V. E.; Munday, J. N.; Atwater, H. A. (Adv. Mater., 2010)

(untitled) - Sreekanth, K. V.; Sidharthan, R.; Murukeshan, V. M. (J. Appl. Phys., 2011)

(untitled) - Ferry, V. E.; Verschuuren, M. A.; Li, H. B. T.; Verhagen, E.; Walters, R. J.; Schropp, R. E. I.; Atwater, H. A.; Polman, A. (Opt. Express, 2010)

(untitled) - Catchpole, K. R.; Polman, A. (Opt. Express, 2008)

(untitled) - Oja Acik, I.; Otto, K.; Krunks, M.; Tõnsuaadu, K.; Mere, A. (J. Therm. Anal. Calorim., 2013)

(untitled) - Kärber, E.; Katerski, A.; Oja Acik, I.; Mikli, V.; Mere, A.; Krunks, M. (Thin Solid Films, 2013)

(untitled) - Kärber, E.; Abass, A.; Khelifi, S.; Burgelman, M.; Katerski, A.; Krunks, M. (Sol. Energy, 2013)

(untitled) - Otto, K.; Oja Acik, I.; Krunks, M.; Tõnsuaadu, K.; Mere, A. (J. Therm. Anal. Calorim., 2014)

(untitled) - Katerski, A.; Kärber, E.; Oja Acik, I.; Dolgov, L.; Mere, A.; Sildos, I.; Mikli, V.; Krunks, M. (Nanoscale Res. Lett., 2014)

(untitled) - Kim, S.-S.; Na, S.-I.; Jo, J.; Kim, D.-Y.; Nah, Y.-C. (Appl. Phys. Lett., 2008)

(untitled) - Yang, J.; You, J.; Chen, C.-C.; Hsu, W.-C.; Tan, H.-R.; Zhang, X. W.; Hong, Z.; Yang, Y. (ACS Nano, 2011)

(untitled) - Brown, M. D.; Suteewong, T.; Kumar, R. S. S.; D’Innocenzo, V.; Petrozza, A.; Lee, M. M.; Wiesner, U.; Snaith, H. J. (Nano Lett., 2011)

(untitled) - Hou, W.; Pavaskar, P.; Liu, Z.; Theiss, J.; Aykol, M.; Cronin, S. B. (Energy Environ. Sci., 2011)

(untitled) - Lim, C.-S.; Im, S. H.; Kim, H.; Chang, J. A.; Lee, Y. H.; Seok, S. I. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Krunks, M.; Kärber, E.; Katerski, A.; Otto, K.; Oja Acik, I.; Dedova, T.; Mere, A. (Sol. Energy Mater. Sol. Cells, 2010)

(untitled) - Thai, T. T.; Hung, P. P.; Son, V. T.; Bich, V. T. (Commun. Phys. (Hanoi, Viet Nam), 2012)

(untitled) - Repan, T.; Dolgov, L.; Katerski, A.; Oja Acik, I.; Kärber, E.; Mere, A.; Mikli, V.; Krunks, M.; Sildos, I. (Appl. Phys. A, 2014)

(untitled) - Rakić, A. D.; Djurišić, A. B.; Elazar, J. M.; Majewski, M. L. (Appl. Opt., 1998)

(untitled) - Alonso, M. I.; Wakita, K.; Pascual, J.; Garriga, M.; Yamamoto, N. (Phys. Rev. B, 2001)